Preparation method and application of MIL-101 (Fe) / Bi2S3 photocatalytic composite material
By preparing the MIL-101(Fe)/Bi2S3 photocatalytic composite material, using its heterojunction structure to excite electron-hole pairs under visible light, and generate active free radicals, it solves the problem that the prior art is difficult to efficiently remove printing and dyeing wastewater and antibiotic pollutants, and achieves efficient wastewater treatment effect.
Patent Information
- Application Number
- CN202411935017.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to efficiently remove printing and dyeing wastewater and antibiotic pollutants, especially when traditional physical, chemical and biological treatment technologies cannot be effectively removed.
Using MIL-101(Fe)/Bi2S3 photocatalytic composite material, by loading Bi2S3 on MIL-101(Fe), a heterojunction is formed, the visible light absorption range is broadened, the photocatalytic activity is enhanced, and electron-hole pairs are excited under visible light irradiation to generate active free radicals for pollutant degradation.
It has achieved efficient catalyzing of the degradation of rhodamine B and tetracycline hydrochloride under mild conditions and can react under sunlight, providing a new wastewater treatment solution, which significantly improves the treatment effect.
Smart Images

Figure CN119657223A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and specifically relates to a preparation method and application of a MIL-101(Fe) / Bi2S3 photocatalytic composite material. Background Art
[0002] Printing and dyeing wastewater usually contains organic pollutants with high chromaticity, strong toxicity and difficulty in degradation. How to effectively treat printing and dyeing wastewater has become an important research direction in the current field of environmental engineering.
[0003] On the other hand, with the widespread use of antibiotics by humans, antibiotic pollutants have begun to enter the water environment and become emerging pollutants in water bodies. These pollutants are difficult to effectively remove through traditional physical, chemical and biological treatment technologies, and may lead to the emergence of drug-resistant bacteria, further threatening public health and safety. Therefore, how to effectively degrade antibiotic pollutants in water has also attracted widespread attention.
[0004] Metal-Organic Frameworks (MOFs) are a class of porous crystalline materials composed of metal ions or metal clusters and organic ligands through coordination bonds. Due to their unique structural properties, such as high specific surface area, adjustable pore size, good chemical stability and high adjustability, MOFs have been widely used in gas storage, catalysis, drug delivery and degradation of environmental pollutants.
[0005] In the field of wastewater treatment, MOFs have shown excellent catalytic performance by introducing specific metal centers (such as Fe, Cu, Ti, etc.) and organic ligands. In the photocatalytic degradation of organic pollutants and antibiotics, MOFs can absorb ultraviolet or visible light to stimulate photogenerated electrons and holes, thereby generating strong oxidizing free radicals such as hydroxyl radicals (•OH) and superoxide anions (•O2 - ). These free radicals can quickly degrade complex organic molecules, further purifying the water.
[0006] Photo-Fenton degradation technology is an advanced oxidation technology based on the Fenton reaction. 2+ / Fe 3+ It catalyzes the decomposition of hydrogen peroxide (H2O2) to produce highly oxidizing hydroxyl radicals (•OH), thereby effectively degrading organic pollutants. 3+ Reduced to Fe 2+ , further increasing the generation rate of hydroxyl radicals and enhancing the reaction efficiency.
[0007] Photo-Fenton technology has a high degradation efficiency, especially in the treatment of printing and dyeing wastewater and antibiotic pollutants, showing significant advantages. Compared with the traditional Fenton reaction, the photo-Fenton reaction not only increases the oxidation rate by introducing light energy, but also expands its applicable pH range and reduces the treatment cost. Therefore, the combination of photo-Fenton technology and MOFs materials has become an emerging hot research direction for the treatment of printing and dyeing wastewater and antibiotic pollution in recent years. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a preparation method and application of a MIL-101(Fe) / Bi2S3 photocatalytic composite material.
[0009] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a method for preparing a MIL-101(Fe) / Bi2S3 photocatalytic composite material, comprising the following steps: Dissolving bismuth nitrate into a bismuth nitrate solution, adding thiourea to the bismuth nitrate solution, stirring evenly, putting the solution into a reaction kettle, and heating the solution in a heater to obtain Bi2S3; centrifuging, washing, and drying the Bi2S3 to obtain Bi2S3 powder; Dissolve terephthalic acid and ferric chloride hexahydrate in N,N-dimethylformamide, add Bi2S3 powder, stir, and obtain a mixed solution; transfer the mixed solution to a reaction kettle, place it in a heater, and react at a constant temperature to obtain a mixture; The reactor was cooled to room temperature, and the mixture was centrifuged, washed, dried, and activated to obtain a MIL-101(Fe) / Bi2S3 photocatalytic composite material.
[0010] In one embodiment, when dissolving bismuth nitrate into a bismuth nitrate solution, bismuth nitrate is dissolved in water, and the mass of bismuth nitrate added per milliliter of water is 0.08-0.1 g.
[0011] In one embodiment, when thiourea is added to the bismuth nitrate solution, the mass of thiourea added to each milliliter of bismuth nitrate solution is 0.01-0.03 g.
[0012] In one embodiment, thiourea is added to a bismuth nitrate solution, stirred at 40-60° C. for at least 1 hour, and then placed in a reactor after being stirred evenly, and placed in a heater for reaction, the heater temperature is set to 160-200° C., and the reaction time is 20-24 hours to obtain Bi2S3; The Bi2S3 was centrifuged, washed, and dried at 60°C~100°C to obtain Bi2S3 powder.
[0013] In one embodiment, the mass ratio of terephthalic acid to ferric chloride hexahydrate is 1:2-1:5.
[0014] In one embodiment, the mass of terephthalic acid added to each milliliter of N,N-dimethylformamide is 0.01-0.05 g.
[0015] In one embodiment, the mass ratio of Bi2S3 powder to terephthalic acid is 1:1~1:15.
[0016] In one embodiment, terephthalic acid and ferric chloride hexahydrate are dissolved in N,N-dimethylformamide, and Bi2S3 powder is added and stirred for 1 to 2 hours to obtain a mixed solution; the mixed solution is transferred to a reactor and placed in a heater with the heater temperature set to 120 to 140°C. The reaction time is 20 to 30 hours to obtain a mixture.
[0017] In one embodiment, the mixture is centrifuged, washed, dried at 50-90° C., and activated; wherein the activation is performed in a vacuum dryer, the temperature of the vacuum dryer is set at 140-160° C., and the working time is 8-12 hours.
[0018] In a second aspect, the present invention provides a MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared by the aforementioned preparation method.
[0019] In a third aspect, the present invention provides a MIL-101(Fe) / Bi2S3 photocatalytic composite material for use in degrading organic dyes and / or antibiotic pollutants, wherein the organic dyes include rhodamine B and the antibiotic pollutants include tetracycline hydrochloride; wherein the MIL-101(Fe) / Bi2S3 photocatalytic composite material is obtained by the aforementioned preparation method.
[0020] It should be noted that the present invention uses a simple solvothermal method to load Bi2S3 on MIL-101(Fe), and the loaded composite material forms a heterojunction, which broadens the visible light absorption range of MIL-101(Fe) and enhances the visible light utilization ability of the composite material. Visible light excites electron-hole pairs to generate active free radicals, which degrade rhodamine B and tetracycline hydrochloride, thereby achieving the purpose of purifying wastewater.
[0021] In one embodiment, when the MIL-101(Fe) / Bi2S3 photocatalytic composite material is used to degrade organic dyes and / or antibiotic pollutants, hydrogen peroxide is also added.
[0022] It should be noted that the present invention combines MOFs materials with photo-Fenton technology to further improve the degradation efficiency of pollutants. MOFs can not only improve the efficiency of photo-Fenton reaction, but also achieve adsorption and catalytic degradation of specific pollutants by regulating the structure, thereby significantly improving the treatment effect. This new composite material has great application potential in treating printing and dyeing wastewater and antibiotic pollutants.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared by the present invention has high-efficiency photocatalytic activity, a wide range of light absorption and good chemical stability. The composite material can effectively catalyze the degradation of rhodamine B and tetracycline hydrochloride under mild conditions, and can react under sunlight, providing a new wastewater treatment solution. By establishing a photocatalytic system of the MIL-101(Fe) / Bi2S3 photocatalytic composite material, a new idea is provided for the degradation of organic dyes and antibiotic pollutants.
[0024] In addition, the difficulties in preparing MIL-101(Fe) / Bi2S3 photocatalytic composite materials are: 1) The loading of Bi2S3 is prone to unevenness, especially when it is overloaded, it will cause aggregation, thus affecting the utilization of active sites. 2) In the existing technology, MOFs have the problem of weak coordination between metal nodes and organic ligands. Under harsh reaction conditions such as organic / aqueous solvents or acidic and alkaline environments or high temperatures, the catalyst has low activity and is difficult to recover. 3) The interface bonding quality of the composite material has a direct impact on the photocatalytic performance. If the interface bonding is not tight, the electron transfer efficiency will be reduced, which will in turn affect the catalytic effect.
[0025] The present invention has mild reaction and simple steps, and successfully prepares a composite material. It can be clearly seen from the detection and attached drawings that Bi2S3 is in the form of nanorods, Bi2S3 is relatively evenly distributed, and there is no obvious agglomeration phenomenon between them. Moreover, the pores of MIL-101(Fe) are unobstructed, the framework is stable, and the reaction molecules can be effectively adsorbed, so that Bi2S3 is tightly and evenly attached to the surface of MIL-101(Fe), the combination is tight, the interface is stable, and the transfer efficiency of electrons at the heterojunction interface is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0027] Figure 1 This is a scanning electron microscope (SEM) spectrum of the photocatalytic composite material prepared by the present invention; Figure 2 The X-ray diffraction (XRD) spectrum of the photocatalytic composite material prepared by the present invention; Figure 3 This is the infrared absorption (FTIR) spectrum of the photocatalytic composite material prepared by the present invention; Figure 4The photocatalytic degradation diagram of TCH by three different materials in the present invention; Figure 5 The photocatalytic degradation diagram of Rhodamine B by three different materials in the present invention; Figure 6 The photocatalytic degradation diagram of TCH at different dosages of the photocatalytic composite material prepared by the present invention; Figure 7 The photocatalytic degradation diagram of Rhodamine B at different dosages of the photocatalytic composite material prepared by the present invention; Figure 8 The photocatalytic degradation diagram of TCH by the photocatalytic composite materials with different proportions prepared by the present invention; Fig. 9 The photocatalytic degradation diagram of Rhodamine B by the photocatalytic composite materials with different proportions prepared by the present invention; Fig.10 The X-ray photoelectron (XPS) spectrum of the photocatalytic composite material prepared by the present invention; Fig.10 In the equation (a)-(f), we can express it as Fig.10 a, 10b, 10c, 10d, 10e, 10f; Fig.10 a is the total spectrum, Fig.10 b is the Fe 2p spectrum, Fig.10 c is the Bi 4f spectrum, Fig.10 d is the C 1s spectrum, Fig.10 e is the O 1s spectrum, Fig.10 f is the S 2p spectrum. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] Unless otherwise specified, the experimental methods used below are conventional methods. The equipment, materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. The principles or mechanisms of equipment that can be purchased through commercial channels are well known and therefore will not be elaborated on.
[0030] Example 1 The preparation method of MIL-101(Fe) / Bi2S3 photocatalytic composite material comprises the following specific steps: First, prepare Bi2S3 powder: dissolve 4.8g of bismuth nitrate in 100ml of distilled water to obtain bismuth nitrate solution. Add 1.5g of thiourea to the bismuth nitrate solution, stir at 60°C for 60min, then put the solution into a Teflon autoclave and keep it at 180°C for 20h to obtain Bi2S3. Separate the obtained Bi2S3 with a centrifuge, wash it with distilled water for several times, and finally wash it with ethanol. After washing, dry it at 100°C for 24h to obtain Bi2S3 powder.
[0031] Then, the MIL-101(Fe) / Bi2S3 composite material was prepared: 0.427g of terephthalic acid and 1.461g of FeCl3•6H2O (ferric chloride hexahydrate) were dissolved in 30mL of N,N-dimethylformamide, and 0.034g of Bi2S3 powder was added, and then stirred continuously at room temperature for 1h to obtain a mixed solution. Then, the mixed solution was transferred to a reactor lined with polytetrafluoroethylene, placed in an oven at 120℃, and reacted at a constant temperature for 24 hours to obtain a mixture. After that, the reactor was cooled to room temperature, the obtained mixture was centrifuged, and after centrifugation, it was repeatedly washed with DMF and anhydrous ethanol. Then, the washed mixture was placed in an oven at 70℃ for drying, and finally activated in a vacuum dryer at 150℃ for 10 hours to obtain a MIL-101(Fe) / Bi2S3 nanocomposite material, namely, a MIL-101(Fe) / Bi2S3 photocatalytic composite material.
[0032] Detection: The MIL-101(Fe) / Bi2S3 photocatalytic composite material was detected in an electron microscope. The image in the SEM is as follows: Figure 1 shown.
[0033] It should be noted that the parameters have been indicated in the figure. The parameters of SEM are specifically described as follows: HV (High Voltage, electron beam acceleration voltage): 10.00kV; mag (Magnification): 50000x, i.e. 50000 times; W / D (Working Distance): 12.6 mm; det (Detector): ETD (Everhart-Thornley Detector); HRW (High Resolution Width): 8.29 μm; frame (Frame Time, scanning time / frame time): 32.6 s; Scale bar length: 3 μm; HiRes Gold on Carbon: Samples are gold-coated and placed on a carbon substrate to enable high-resolution imaging.
[0034] Refer to Figure 2-Figure 3 : Depend on Figure 2 It can be seen that the XRD patterns of the MIL-101(Fe) / Bi2S3 photocatalytic composite materials show the characteristic peaks of MIL-101(Fe) and Bi2S3, without too many impurity peaks, which proves that the composite material was successfully synthesized.
[0035] Among them, X-ray diffraction instrument parameters related to XRD pattern: (1) Manufacturer model: Bruker AXS GmbH, Germany, D8 ADVANCE; (2) Test conditions: Cu target Ka ray, minimum readable step 0.0001°, test degree range 5°-80°, speed 5° / min.
[0036] Depend on Figure 3 It can be seen from the infrared spectrum of the MIL-101(Fe) / Bi2S3 photocatalytic composite material that the structural properties of the MIL-101(Fe) / Bi2S3 composite material have partially changed, but MIL-101(Fe) is still the main body, and the characteristic absorption peaks are basically retained, further proving the successful synthesis of the MIL-101(Fe) / Bi2S3 photocatalytic composite material.
[0037] Among them, infrared spectrum instrument parameters related to infrared spectrum: (1) Manufacturer model: Bruker AXS GmbH, Germany, InvenioS; (2) Test conditions: Scanning range 4000-500 cm -1 .
[0038] Next, the synthesized MIL-101(Fe) / Bi2S3 photocatalytic composite material is subjected to performance testing, and the application of the MIL-101(Fe) / Bi2S3 photocatalytic composite material is reflected through the performance testing.
[0039] Example 2 Preparation of MIL-101(Fe) material: 0.427g of terephthalic acid and 1.461g of FeCl3•6H2O (ferric chloride hexahydrate) were dissolved in 30mL of N,N-dimethylformamide, and then stirred continuously at room temperature for 1h to obtain a mixed solution. Then, the mixed solution was transferred to a reactor lined with polytetrafluoroethylene, placed in an oven at 120°C, and reacted at a constant temperature for 24 hours to obtain a mixture. After that, the reactor was cooled to room temperature, the resulting mixture was centrifuged, and after centrifugation, it was repeatedly washed with DMF and anhydrous ethanol. Then, the washed mixture was placed in an oven at 70°C for drying, and finally activated in a vacuum dryer at 150°C for 10 hours to obtain MIL-101(Fe) material.
[0040] Example 3 In this example, a photocatalytic experiment was performed: (1) Degradation of TCH by MIL-101(Fe) / Bi2S3 photocatalytic composite material: The photocatalytic activity of the MIL-101(Fe) / Bi2S3 photocatalytic composite material was evaluated by degrading TCH under visible light irradiation (λ>400nm). The specific steps are as follows: The reaction beaker and the light source are set in the reaction box, and a 300W UV-visible lamp with a cut-off filter of λ>400 nm is used as the light source. The outer wall of the reaction beaker is wrapped with tin foil to shield the surrounding light, and the light source is set vertically above the reaction beaker, about 100 mm away from the reaction beaker.
[0041] The experiment was carried out at room temperature (25℃±2℃). 50ml of 20mg / L TCH solution was added to a 100mL reaction beaker, and then 0.015g of catalytic material and 0.5ml of 0.1mol / L hydrogen peroxide were added. The suspension was stirred in the dark to obtain a suspension. Before the start of photocatalytic degradation, the suspension was subjected to light-proof adsorption reaction for 30min to achieve adsorption / desorption equilibrium. Then the light source was started for photocatalytic reaction. Every 30min, 3ml of the suspension was taken out with a syringe, filtered with a 0.22μL water filter, and then the absorbance of the pollutant at 357nm was measured on a UV-visible spectrophotometer (Mapada P1, Shanghai Meipuda Instrument Co., Ltd., China). The TCH degradation rate was calculated according to the TCH degradation rate formula.
[0042] In the above, the catalytic materials are Bi2S3 material or MIL-101(Fe) material or the MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared in Example 1; wherein the Bi2S3 material is the Bi2S3 powder prepared in Example 1. The MIL-101(Fe) material is the MIL-101(Fe) material prepared in Example 2. TCH (tetracycline hydrochloride) was purchased from Aladdin with a purity of 96%.
[0043] In addition, the maximum absorption wavelength of TCH is 357nm, and the degradation rate of TCH is as follows: η=[(C0-C) / C0]×100% Where: η is the degradation rate of TCH; C is the absorbance after TCH degradation; C0 is the absorbance before TCH degradation.
[0044] It should be noted that in this experiment, different catalytic materials were used to degrade TCH and the degradation of different materials was investigated.
[0045] Results reference Figure 4 , Bi2S3 material, MIL-101(Fe) material and the MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared in Example 1 degraded TCH. The degradation rate of TCH by MIL-101(Fe) / Bi2S3 photocatalytic composite material could reach 95.7% after 120 minutes of reaction, while the degradation rates of TCH by Bi2S3 material and MIL-101(Fe) material were about 10% and 37% respectively after 120 minutes of reaction, indicating the excellent degradation effect of MIL-101(Fe) / Bi2S3 photocatalytic system on TCH.
[0046] Figure 4 C is the absorbance after TCH degradation; C0 is the absorbance before TCH degradation.
[0047] (2) Degradation of RhB (Rhodamine B) by MIL-101(Fe) / Bi2S3 photocatalytic composite material: The photocatalytic activity of the MIL-101(Fe) / Bi2S3 photocatalytic composite material was evaluated by degrading RhB under visible light irradiation (λ>400nm). The specific steps are as follows: The reaction beaker and the light source are set in the reaction box, and a 300W UV-visible lamp with a cut-off filter of λ>400 nm is used as the light source. The outer wall of the reaction beaker is wrapped with tin foil to shield the surrounding light, and the light source is set vertically above the reaction beaker, about 100 mm away from the reaction beaker.
[0048] The experiment was carried out at room temperature (25℃±2℃). 50ml of RhB solution was added to a 100ml reaction beaker, and then 0.015g of catalytic material and 1ml of 0.1mol / L hydrogen peroxide were added. The suspension was stirred in the dark to obtain a suspension. Before the start of photocatalytic degradation, the suspension was subjected to light-proof adsorption reaction for 30min to achieve adsorption / desorption equilibrium. Then the light source was started for photocatalytic reaction. Every 30min, 3ml of the suspension was taken out with a syringe, filtered with a 0.22μL water filter, and then its absorbance at 554nm was measured on a UV-visible spectrophotometer. The RhB degradation rate was calculated according to the formula of RhB degradation rate.
[0049] In the above, the catalytic materials are Bi2S3 material or MIL-101(Fe) material or MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared in Example 1; wherein the Bi2S3 material is the Bi2S3 powder prepared in Example 1. The MIL-101(Fe) material is the MIL-101(Fe) material prepared in Example 2. RhB (rhodamine B) was purchased from Sigma Aldrich, 95%.
[0050] In addition, the maximum absorption wavelength of RhB is 554nm, and the formula for the degradation rate of RhB is as follows: η=[(C0-C) / C0]×100% Where: η is the degradation rate of RhB; C is the absorbance after RhB degradation; C0 is the absorbance before RhB degradation.
[0051] It should be noted that in this experiment, different catalytic materials were used to degrade RhB and the degradation of different materials was investigated.
[0052] Results reference Figure 5 , Bi2S3 material, MIL-101(Fe) material and the MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared in Example 1 degraded RhB. The degradation rate of RhB by MIL-101(Fe) / Bi2S3 photocatalytic composite material could reach 98.6% after 90 minutes of reaction, while the degradation rates of RhB by Bi2S3 material and MIL-101(Fe) material were about 28% and 62% respectively after 90 minutes of reaction, indicating the excellent degradation effect of MIL-101(Fe) / Bi2S3 photocatalytic system on RhB.
[0053] Figure 5 C is the absorbance after RhB degradation; C0 is the absorbance before RhB degradation.
[0054] (3) In order to understand the effect of the addition amount of MIL-101(Fe) / Bi2S3 photocatalytic composite material on the photocatalytic degradation of TCH, the following experiments were conducted to observe the catalyst effect: The photocatalytic activity of the MIL-101(Fe) / Bi2S3 photocatalytic composite material was evaluated by degrading TCH under visible light irradiation (λ>400nm). The specific steps are as follows: The reaction beaker and the light source are set in the reaction box, and a 300W UV-visible lamp with a cut-off filter of λ>400 nm is used as the light source. The outer wall of the reaction beaker is wrapped with tin foil to shield the surrounding light, and the light source is set vertically above the reaction beaker, about 100 mm away from the reaction beaker.
[0055] The experiment was carried out at room temperature (25°C ± 2°C). 50 ml of 20 mg / L TCH aqueous solution was added to a 100 mL reaction beaker, and then different concentrations of 0.1 g / L, 0.2 g / L, 0.3 g / L, and 0.4 g / L of composite catalyst (MIL-101 (Fe) / Bi2S3 photocatalytic composite material prepared in Example 1) were added to the TCH aqueous solution, and then 0.5 ml of 1 mol / L hydrogen peroxide was added. Stir in the dark to obtain a suspension. Before the start of photocatalytic degradation, the suspension was subjected to light-proof adsorption reaction for 20 minutes to achieve adsorption / desorption equilibrium. Then the light source was started for photocatalytic reaction, and 3 ml of the suspension was taken out with a syringe every 30 minutes, filtered with a 0.22 μL water filter, and then the absorbance of the pollutant at 357 nm was measured on a UV-visible spectrophotometer, and the TCH degradation rate was calculated according to the formula of TCH degradation rate.
[0056] In the above, TCH (tetracycline hydrochloride) was purchased from Aladdin with 96% purity.
[0057] In addition, the maximum absorption wavelength of TCH is 357nm, and the degradation rate of TCH is as follows: η=[(C0-C) / C0]×100% Where: η is the degradation rate of TCH; C is the absorbance after TCH degradation; C0 is the absorbance before TCH degradation.
[0058] Results reference Figure 6 It can be obtained that, within a certain range, the more the composite catalyst is added, the better the photocatalytic effect at the beginning of the reaction; but as the catalyst dosage increases, too much catalyst will have a shielding effect, which is not conducive to the final degradation effect. Figure 6 C is the absorbance after TCH degradation; C0 is the absorbance before TCH degradation.
[0059] (4) In order to understand the effect of the addition amount of MIL-101(Fe) / Bi2S3 photocatalytic composite material on the photocatalytic degradation of RhB, the following experiments were conducted to observe the catalyst effect: The photocatalytic activity of the MIL-101(Fe) / Bi2S3 photocatalytic composite material was evaluated by degrading RhB under visible light irradiation (λ>400nm). The specific steps are as follows: The reaction beaker and the light source are set in the reaction box, and a 300W UV-visible lamp with a cut-off filter of λ>400 nm is used as the light source. The outer wall of the reaction beaker is wrapped with tin foil to shield the surrounding light, and the light source is set vertically above the reaction beaker, about 100 mm away from the reaction beaker.
[0060] The experiment was carried out at room temperature (25°C ± 2°C). 50 ml of 40 mg / L RhB aqueous solution was added to a 100 mL reaction beaker, and then different concentrations of 0.1 g / L, 0.2 g / L, 0.3 g / L, and 0.4 g / L of composite catalyst (MIL-101 (Fe) / Bi2S3 photocatalytic composite material prepared in Example 1) were added to the RhB aqueous solution, and then 1 ml of 1 mol / L hydrogen peroxide was added. Stir in the dark to obtain a suspension. Before the start of photocatalytic degradation, the suspension was subjected to light-proof adsorption reaction for 30 minutes to achieve adsorption / desorption equilibrium. Then the light source was started for photocatalytic reaction, and 3 ml of the suspension was taken out with a syringe every 30 minutes, filtered with a 0.22 μL water filter, and then the absorbance of the pollutant at 554 nm was measured on a UV-visible spectrophotometer, and the RhB degradation rate was calculated according to the formula of the RhB degradation rate.
[0061] In the above, RhB (Rhodamine B) was purchased from Sigma Aldrich, 95%.
[0062] In addition, the maximum absorption wavelength of RhB is 554nm, and the formula for the degradation rate of RhB is as follows: η=[(C0-C) / C0]×100% Where: η is the degradation rate of RhB; C is the absorbance after RhB degradation; C0 is the absorbance before RhB degradation.
[0063] Results reference Figure 7 It can be obtained that, within a certain range, the more the composite catalyst dosage is, the better the photocatalytic effect is; but as the catalyst dosage increases, the degradation effect reaches saturation, and there is no significant change or even affects the degradation effect.
[0064] Figure 7 C is the absorbance after RhB degradation; C0 is the absorbance before RhB degradation.
[0065] Next, the addition amount of Bi2S3 and MIL-101(Fe) was adjusted to synthesize composite materials with different ratios. The composite materials are marked as Xw%, where X represents the different mass percentages of Bi2S3 in the composite material (x=5, 10, 15).
[0066] Example 4 Referring to the preparation method of Example 1, the difference from Example 1 is that in "preparing the MIL-101(Fe) / Bi2S3 composite material", the amount of Bi2S3 powder added is changed, and the mass proportion of Bi2S3 powder in the MIL-101(Fe) / Bi2S3 composite material is 5%, and a 5% composite material is obtained. The rest is the same as Example 1.
[0067] It should be noted that, in order to more clearly implement the technical solution of the present invention, the specific calculation method of 5% is hereby explained: 5%=[mass of Bi2S3 powder / (0.427g+1.461g+mass of Bi2S3 powder)]×100%.
[0068] The subsequent Examples 5 and 6 also refer to this calculation method.
[0069] Example 5 Referring to the preparation method of Example 1, the difference from Example 1 is that in "preparing the MIL-101(Fe) / Bi2S3 composite material", the amount of Bi2S3 powder added is changed, and the mass proportion of Bi2S3 powder in the MIL-101(Fe) / Bi2S3 composite material is 10%, and a 10% composite material is obtained. The rest is the same as Example 1.
[0070] Example 6 Referring to the preparation method of Example 1, the difference from Example 1 is that in "preparing the MIL-101(Fe) / Bi2S3 composite material", the amount of Bi2S3 powder added is changed, and the mass proportion of Bi2S3 powder in the MIL-101(Fe) / Bi2S3 composite material is 15%, and a 15% composite material is obtained. The rest is the same as Example 1.
[0071] Then perform the test: (1) The composite materials of Examples 4 to 6 were subjected to a photocatalytic experiment according to the method of "(1) Degradation of TCH by MIL-101(Fe) / Bi2S3 photocatalytic composite materials" in Example 3, wherein the catalytic materials used were the composite materials of Examples 4 to 6, respectively.
[0072] Results reference Figure 8It can be seen that when degrading TCH solution, the composite materials with different ratios all showed good Fenton performance, among which the best one was the 10w% MIL-101(Fe) / Bi2S3 photocatalytic composite material.
[0073] (2) The composite materials of Examples 4 to 6 were subjected to a photocatalytic experiment according to the method "(2) Degradation of RhB (Rhodamine B) by MIL-101(Fe) / Bi2S3 photocatalytic composite materials" in Example 3, wherein the catalytic materials used were the composite materials of Examples 4 to 6, respectively.
[0074] Results reference Fig. 9 It can be seen that when degrading RhB solution, the composite materials with different ratios also showed good photocatalytic performance, among which the best one was the 10w% MIL-101(Fe) / Bi2S3 photocatalytic composite material.
[0075] Example 7 The elemental composition and chemical state of the MIL-101(Fe) / Bi2S3 photocatalytic composite were further investigated using X-ray photoelectron spectroscopy (XPS) using an X-ray photoelectron spectrometer (Thermo Kalpha).
[0076] XPS measurement spectra of MIL-101(Fe) / Bi2S3, MIL-101(Fe) and Bi2S3 are shown in Figure 2. Fig.10 shown.
[0077] Reference Fig.10 In (a), that is Fig.10 a, Fig.10 a is the overall spectrum. The presence of Bi, S, C, O, and Fe elements confirms the successful combination of Bi2S3 and MIL-101(Fe). Fe, O, and C elements exist in MIL-101(Fe), while Bi, S, O, and C elements are clearly visible in Bi2S3. Fig.10 (b)-(f), that is Fig.10 b- Fig.10 f, according to the changes in the binding energies of Fe 2p, Bi 4f, C 1s, O 1s, and S 2p, it can be well proved that a heterojunction is formed between MIL-101(Fe) and Bi2S3. It can effectively improve the separation efficiency of electrons and holes and prolong the lifetime of active carriers, thereby improving the photocatalytic activity.
[0078] Analysis: Analysis of the degradation mechanism of the composite material: The excellent performance of the MIL-101(Fe) / Bi2S3 photocatalytic composite material is attributed to its unique structural design and synergistic effect. As a typical representative of MOFs materials, MIL-101(Fe) has a high specific surface area and good adsorption performance, and can effectively adsorb pollutants. As a narrow bandgap semiconductor, Bi2S3 has strong light absorption ability under visible light and can effectively excite photogenerated electrons and holes. The present invention successfully constructs a heterojunction structure by introducing Bi2S3 nanoparticles into MIL-101(Fe). The existence of this structure effectively prevents the recombination of photogenerated electrons and holes, thereby improving the photocatalytic activity. In addition, the Fe ions in MIL-101(Fe) can trigger the Fenton reaction during the photocatalytic process, further generating hydroxyl radicals (•OH) with strong oxidizing properties, thereby enhancing the efficiency of degrading organic pollutants.
[0079] Overall, the MIL-101(Fe) / Bi2S3 photocatalytic composite material prepared by the present invention mainly relies on the following reaction mechanism during the photocatalytic process: 1. Bi2S3 generates photogenerated electrons and holes under visible light irradiation.
[0080] 2. The photogenerated electrons are transferred to MIL-101(Fe), inhibiting the electron-hole recombination and improving the photocatalytic efficiency.
[0081] 3. Fe in MIL-101(Fe) 3+ / Fe 2+ The cycle catalyzes the decomposition of H2O2 to generate •OH, accelerating the degradation of pollutants.
[0082] 4. The porous structure of MIL-101(Fe) is conducive to the adsorption of pollutants, thereby increasing the rate of photocatalytic reaction.
[0083] 5. Through the above reaction mechanism, the MIL-101(Fe) / Bi2S3 photocatalytic composite material achieves efficient degradation of RhB and TCH organic pollutants, providing the possibility for further application in the degradation of other pollutants. It shows great research potential and application prospects in the treatment of printing and dyeing wastewater and the degradation of antibiotic pollutants.
[0084] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a MIL-101(Fe) / Bi2S3 photocatalytic composite material, characterized in that: The steps include: Dissolving bismuth nitrate into a bismuth nitrate solution, adding thiourea to the bismuth nitrate solution, stirring evenly, putting the solution into a reaction kettle, and heating the solution in a heater to obtain Bi2S3; centrifuging, washing, and drying the Bi2S3 to obtain Bi2S3 powder; Dissolve terephthalic acid and ferric chloride hexahydrate in N,N-dimethylformamide, add Bi2S3 powder, stir, and obtain a mixed solution; transfer the mixed solution to a reaction kettle, place it in a heater, and react at a constant temperature to obtain a mixture; The reactor was cooled to room temperature, and the mixture was centrifuged, washed, dried, and activated to obtain a MIL-101(Fe) / Bi2S3 photocatalytic composite material.
2. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: When dissolving bismuth nitrate into a bismuth nitrate solution, the bismuth nitrate is dissolved in water, and the mass of bismuth nitrate added per milliliter of water is 0.08-0.1 g.
3. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: When thiourea is added to the bismuth nitrate solution, the mass of thiourea added to each milliliter of bismuth nitrate solution is 0.01~0.03g.
4. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: Add thiourea to the bismuth nitrate solution, stir at 40-60°C for at least 1 hour, put into a reactor after stirring evenly, place in a heater for reaction, set the heater temperature to 160-200°C, and react for 20-24 hours to obtain Bi2S3; The Bi2S3 was centrifuged, washed, and dried at 60°C~100°C to obtain Bi2S3 powder.
5. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: The mass ratio of terephthalic acid to ferric chloride hexahydrate is 1:2~1:
5.
6. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: The mass of terephthalic acid added to each milliliter of N,N-dimethylformamide is 0.01~0.05g.
7. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: The mass ratio of Bi2S3 powder to terephthalic acid is 1:1~1:
15.
8. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: Dissolve terephthalic acid and ferric chloride hexahydrate in N,N-dimethylformamide, add Bi2S3 powder, stir for 1 to 2 hours to obtain a mixed solution; transfer the mixed solution to a reactor, place it on a heater, set the heater temperature to 120 to 140°C, and react for 20 to 30 hours to obtain a mixture.
9. The method for preparing the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to claim 1, characterized in that: The mixture is centrifuged, washed, dried at 50-90°C, and activated; wherein the activation is performed in a vacuum dryer, the temperature of the vacuum dryer is set at 140-160°C, and the working time is 8-12 hours.
10. MIL-101(Fe) / Bi2S3 photocatalytic composite material is used to degrade organic dyes and / or antibiotic pollutants, characterized in that: The organic dye includes rhodamine B, and the antibiotic pollutants include tetracycline hydrochloride; wherein the MIL-101(Fe) / Bi2S3 photocatalytic composite material is prepared according to the preparation method of the MIL-101(Fe) / Bi2S3 photocatalytic composite material according to any one of claims 1-9.